REBUILDING AUTO PIECES BY WELDING IN ULTRASONIC FIELD - Oana CHIVU (Fiabilitate şi Durabilitate)
In the trucks manufacturing industry, railway industry, metallurgy industry, petrochemical and chemical industries are used several reconditioning technologies, the most common being: restoring plastic using deformation, welding, soldering, metallization, cutting through micro-splintering and deposition of non-metallic materials.The problem of reconditioning of the auto parts is a particularly complex and so the probleme arises of finding technical solutions that meet current needs, and in this sense in the paper is approached a technology by reconditioning considering the welding in ultrasonic field.